A brief review of wideband circularly-polarized planar antenna design - Shen, Yizhu (2013)
Wideband circularly-polarized antenna is one of the key components in the wireless systems. This paper briefly reviews the design mechanisms of circularly-polarized antenna, and discusses their advantages and disadvantages. In addition, two circularly-polarized planar antennas for ultra-wideband systems developed in our group are also presented and discussed in this paper.